The Effectiveness of Hypernatural Video-Based Learning Media in Enhancing Students’ Digital Literacy in Social Studies - Asmaul Husni; Fawziah Zahrawati B; Hasmiah Herawaty; Fuad Guntara (STKIP Taman Siswa Bima, 2026)
This study analyzes the effectiveness of hypernatural video-based learning media on students’ digital literacy in Social Studies. A quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design) was employed. The sample consisted of 40 seventh-grade students at SMPN 8 Parepare. Data were collected through questionnaires, observation, and documentation, and analyzed using descriptive and inferential statistics, including a independent samples t-test. The results showed an increase in the mean score from 57.73 to 61.20, with a significance value of 0.005 (p < 0.05), indicating a significant effect. However, the N-Gain score of 0.0661 was categorized as low. These findings suggest that hypernatural video-based learning media effectively improve students’ digital literacy, although the magnitude of improvement remains limited. This study reinforces multimedia learning theory while practically providing a reference for developing innovative, technology-based instructional media.